How Does LG Group Embed Enterprise Risk Management (ERM) System In Its Conglomerate Governance To Control Its Affiliated Firms' Risk Events? - Kim, Sangil; Yoo, Jungmin (Journal of Applied Business Research, 2017)
This paper presents a case of enterprise risk management (ERM) embeddedness in LG Group, globalized conglomerate in Korea. Findings are differentiated from prior studies in two aspects. First, this study focuses on how ERM systems minimize the agency costs between conglomerate headquarters and its affiliated firms. Second, cases of diversified twelve affiliated firms find that COSO ERM framework are to be applied adaptively to entities’ inherent or external conditions as industry, age, management level etc. Those findings might be a practical guidance for most Asian business groups to embed ERM frameworks in conglomerate governances, filling gaps between theoretical COSO manual and practical applications.
Keywords: Enterprise Risk Management; Conglomerate Group; Affiliated Firms; Agency Cost